A review of some Antiretroviral therapies used in Management of HIV/AIDS in Ghana (Bangladesh Journal of Medical Science, 2012)
HIV is a RNA retrovirus that causes progressive weakening of the hosts immune system increasing susceptibility  to opportunistic infections. Antiretroviral drugs are currently used to manage the infection. This  paper reviews the benefits and the toxicity associated with ARTs currently used in Ghana. Google search,  PUBMED and Google scholar were used to gather information from different books, websites and peerreviewed  journal articles. ARTs significantly improved the quality of life of people living with HIV/AIDS  by increasing the CD4 count and reducing the viral load. ARTs have short and long term side effects which  may be life threatening. Toxicity may vary from drug to drug and from one drug class to the other. We conclude  that it is important to select a regimen that is not only effective but also safe. This requires consideration  of not only the toxicity potential of an ARV regimen but also an individual patients underlying conditions,  concomitant medications and history of drug intolerance.   DOI: http://dx.doi.org/10.3329/bjms.v11i3.11716   Bangladesh Journal of Medical Science Vol. 11 No. 03 July12